Analysis of Classical Educational Philosophy Streams in Shaping Modern Educational Paradigms - Hasyim D, Nur Fadhilah Rukmana; Azis, Fatimah; Kaharuddin; Silapa, Sarajuddin (Indonesian Journal Publisher, 2025)
The classical philosophy of education holds a fundamental contribution to shaping the construction of the modern educational paradigm. Major schools of thought such as perennialism, essentialism, progressivism, and reconstructionism play a significant role in directing the development of contemporary educational orientations, both in curriculum formulation and pedagogical application. This study aims to comprehensively analyze the relevance of these classical philosophical traditions in the formation of the modern educational paradigm through a literature-based approach. The research findings indicate that the modern educational paradigm did not emerge instantaneously but is instead the result of an evolutionary interaction between classical philosophical principles and the continuously developing dynamics of socio-cultural change. Key concepts such as the pursuit of universal truth, the importance of mastering essential knowledge, learner-centered instruction, and the significance of critical education serve as foundational elements in the formulation of contemporary educational policies and practices. Thus, this study affirms that classical educational philosophy retains strategic relevance as a conceptual foundation for strengthening the development of a modern education system that emphasizes humanistic values, adaptive capacities, and transformative aims.